Teachers-Centred Distribution of Praziquantel to Control Schistosomiasis in Gezira State, Sudan - Elfatih Mohamed Malik; Abdelhafiz H. Abdalla; Ali O. Babiker; Abbas S. Elmahi; Ahmed E. Abdall; Samira Hamid; Salwa M. Elsanosi; Bakri Nour; Musab S. Elhag; Khalid A. Elmurdi; et al. (Public Health, 2016)
Schistosomiasis is a major public health problem in Gezira State, Sudan. The state-wide prevalence survey among school children showed that the prevalence reached up to 82% in some districts and the reported mean intensity reached up to 223 eggs/gm of stool for S. mansoni and 28 eggs/10 ml of urine for S. haematobium. Based on this, a plan was established to control schistosomiasis. A teacher-centered distribution of praziquantel was organized in 22 districts targeting school pupils only. This short communication describes the intervention, the coverage and lessons learnt. With negligible cost and minimal efforts the target coverage of school pupils with praziquantel was reached by teachers in a demonstrable short time. In the successive two rounds the coverage exceeded 90% of the target school enrolled children. This approach can be extended to target all school and preschool children plus children not attend-ing school in the state, as they represent a very important reservoir for schistosomiasis and soil transmitted helminthes.